2008
DOI: 10.1530/rep-07-0287
|View full text |Cite
|
Sign up to set email alerts
|

Gas6 and the Tyro 3 receptor tyrosine kinase subfamily regulate the phagocytic function of Sertoli cells

Abstract: The apoptotic spermatogenic cells and residual bodies are phagocytosed and degraded by Sertoli cells during spermatogenesis. The mechanisms of this process are largely unknown. Here, we demonstrate that Gas6 and its receptors, the Tyro 3 subfamily of receptor tyrosine kinases (RTKs; Tyro 3, Axl, and Mer), regulate the phagocytic function of Sertoli cells. The phagocytic ability of Sertoli cells increased by five times in the presence of Gas6 in serum-free medium when compared with controls. The Sertoli cells l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
73
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 38 publications
3
73
0
1
Order By: Relevance
“…84,85 Moreover, the Gas6/ProS-TAM system facilitates phagocytic clearance of apoptotic germ cells by SCs. 86 The removal of apoptotic germ cells by phagocytes facilitates the elimination of the auto-antigens, which may reduce endogenous inflammation. We recently demonstrated that damaged germ cells induce endogenous inflammatory responses in the testis.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…84,85 Moreover, the Gas6/ProS-TAM system facilitates phagocytic clearance of apoptotic germ cells by SCs. 86 The removal of apoptotic germ cells by phagocytes facilitates the elimination of the auto-antigens, which may reduce endogenous inflammation. We recently demonstrated that damaged germ cells induce endogenous inflammatory responses in the testis.…”
Section: Immune Privilege In the Testismentioning
confidence: 99%
“…In addition, the Sertoli cell number determines an upper limit for sperm production, a crucial detail (Sharpe, 1994(Sharpe, , 1999Buzzard et al, 2002). Sertoli cells facilitate the progression of degenerating germ cells and their remains (Griswold, 1995;Griswold, 1998;Buzzard et al, 2002;Mruk & Cheng, 2004;Oliveira et al, 2009) and it has been demonstrated that apoptotic spermatogenic cells and residual bodies are phagocytosed and degraded by Sertoli cells during mammalian spermatogenesis (Shiratsuchi et al, 1999;Xiong et al, 2008Xiong et al, , 2009.…”
Section: The Sertoli Cellmentioning
confidence: 99%
“…During mammalian spermatogenesis, more than 75% of developing spermatogenic cells undergo apoptosis before maturation. 1 Moreover, under certain pathological conditions, apoptosis is very likely to occur in specific germ cells (GCs). 2 De facto the quantity of GCs is tightly regulated to match the supportive capacity of Sertoli cells (SCs).…”
mentioning
confidence: 99%